Polymer nanocomposite foams - Mittal, Vikas (CRC Press/Taylor & Francis, 2014)
"Featuring contributions from experts in the field, this book provides information on the application of composite nanotechnology for making functional foams to serve various applications. It does not just explain the synthesis of bulk nanocomposite materials, but goes a step further in describing the application of nanotechnology. Foams generated with polymer nanocomposite materials have a variety of applications in many fields, including automotive, packaging, and insulation. The use of nanocomposites in the formation of foams enhances property profiles like porosity control, strength, and stiffness significantly, which enables the application of such materials ranging from conventional to more advanced areas. Information on various polymer nanocomposite foams has previously been available mainly in the form of research studies, and a comprehensive book describing these materials and their technologies has not been available. This book compiles advances in the various aspects of nanocomposite foams to provide background information to readers new to this field, as well as to serve as a reference text for researchers in this area. "--